2019
DOI: 10.1080/1360144x.2019.1663352
|View full text |Cite
|
Sign up to set email alerts
|

Successful development programs for experienced doctoral supervisors – What does it take?

Abstract: In this paper, we focus on professional development for senior academic staff, in particular, doctoral supervisors. Using an authentic case as an example of a long-term, comprehensive, and mandatory development program for senior staff, we analyse the challenges and benefits of such a program and identify issues for consideration. The main issues include: 1) the need for strong incentive structures initiated by the top management; 2) teaching principles that are aligned with the group of senior academics;and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, both experienced and unexperienced supervisors seem to be able to develop as supervisors. Wichmann-Hansen et al (2020) have also found several positive impacts for experienced supervisors who attended a long-term mandatory development programme on: (a) supervisors' competence development and learning, (b) the local supervision culture, and (c) indirect effects on doctoral researchers' satisfaction with their supervisors. Formal professional programmes might also create problems described by supervisors, such as loneliness, insecurity, lack of rights, distress, and feelings of incompetence as a supervisor (Emilsson & Johnsson, 2007).…”
Section: Supervision As Professional Workmentioning
confidence: 96%
See 2 more Smart Citations
“…However, both experienced and unexperienced supervisors seem to be able to develop as supervisors. Wichmann-Hansen et al (2020) have also found several positive impacts for experienced supervisors who attended a long-term mandatory development programme on: (a) supervisors' competence development and learning, (b) the local supervision culture, and (c) indirect effects on doctoral researchers' satisfaction with their supervisors. Formal professional programmes might also create problems described by supervisors, such as loneliness, insecurity, lack of rights, distress, and feelings of incompetence as a supervisor (Emilsson & Johnsson, 2007).…”
Section: Supervision As Professional Workmentioning
confidence: 96%
“…For mandatory development programmes to work, several researchers assert that a strong incentive structure from top management is essential, especially for experienced supervisors (Lee, 2018;Wichmann-Hansen et al, 2020). However, considerable resistance to compulsory centralised and formal professional development programmes is also evident, especially from more experienced supervisors who are often 'allergic' to programmes that could be interpreted as related to a quality assurance agenda of governments and university administrators (Manathunga et al, 2010;Wichmann-Hansen et al, 2020, p. 5).…”
Section: Supervision As Professional Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hartanti and Purwanto (2019); (Fye et al, 2020) The following are included in the planning for implementing academic supervision: (a) managing the curriculum; (b) achieving the requirements for both content and procedure; (c) assessing learning; and (d) evaluating the caliber of learning. The following are included in the planning for implementing academic supervision: curriculum management, achieving content and procedural requirements, learning evaluation, reviewing the caliber of learning, (Daryanto & Rachmawati, 2015); (Wichmann-Hansen et al, 2020), Give examples of how to develop an academic supervision program using the following guiding principles: (a) objective (data as is); (b) be responsible; (c) sustainable; (d) based on the National Education Standards (NES); and (e) based on the needs and conditions of the school. The ability of the instructor to plan, implement, evaluate learning outcomes, use assessment data to improve learning services, create an enjoyable learning environment, use the resources that are available for learning, and generate suitable learning interactions is the major goal of academic supervision (strategies, methods, techniques).…”
Section: Academic Supervision Planningmentioning
confidence: 99%